Pattern of orthopaedic case presentations at the rivers state university teaching hospital: a ten-year review - Aaron, Friday E.; Ijah, Rex Friday Ogoronte A.; Obene, Tonye (International Surgery Journal, 2022)
Background: Pattern of diseases help institutions and governments to know the dominant disease conditions and how to allocate scarce resources. Knowledge of the pattern of orthopedic disease conditions seen and treated in the Rivers State university teaching hospital will help in guiding the repositioning effort of the department/discipline, especially in the light of the new status of the institution as a teaching hospital for teaching, service delivery and research. The aim of this study therefore was to determine the pattern of orthopedic cases seen in the surgery department of the Rivers State university teaching hospital from January 2010 to January 2019. Methods: A descriptive retrospective cross-sectional study was carried out at the emergency room, clinic, operating theatre, and wards of the surgery department of the Rivers State university teaching hospital, using hospital registers. The study was analyzed using the Microsoft excel spreadsheet. Results: There were 2854 orthopedic emergency room cases seen, comprising 621 fractures, 463 lumbar spondylosis/ spondylolisthesis, 392-foot ulcer/sepsis, 375 dislocations, 310 acute osteomyelitis, and 864 osteoarthritis with other conditions. The common orthopedic cases seen in the out-patient clinics in descending order of occurrence were lumbar spondylitis / spondylolisthesis (881), osteoarthritis (655), fractures (560), dislocations (227), etc. Conclusions: Trauma-related disease care constituted the bulk of work of the orthopedic surgeon in our environment in the emergency room, operating theatre and ward admissions, and younger males were more affected.